Spring plankton energy content by size classes in two contrasting environments of a high latitude ecosystem: The Beagle Channel - Bruno, Daniel Osvaldo; Valencia Carrasco, Laura Constanza; Paci, María Antonella; Leonarduzzi, Ezequiel; Castro, Pablo Leonardo; Riccialdelli, Luciana; Iachetti, Clara Margarita; Cadaillón, Andreana Mackenna; Giesecke Astorga, Claudio Ricardo; Schloss, Irene Ruth; Berghoff, Carla Florencia; Martín de Nascimento, Jacobo; et al. (Journal of Marine Systems)
This study aimed to characterize the energy density (ED), using a micro-bomb calorimeter, of different plankton fractions: microplankton (23–67 μm; including phytoplankton and small heterotrophs), microzooplankton (67–200 μm), mesozooplankton (200–2000 μm), and fish larvae, at two micro-basins separated by a sill (the Mackinlay Strait) and with different topography and hydrography in the Beagle Channel. For that purpose, two sampling sites (west (F1) and east (F2) of the Mackinlay Strait), two strata (surface and near-bottom layers) and diel variations (diurnal and nocturnal hours) were considered. Also, patterns among plankton fractions´ ED and water properties (temperature, salinity, total alkalinity, pH, and dissolved inorganic carbon) were analysed by redundancy analysis. ED values of the plankton fractions differed among sites, strata and sampling time. Surface microplankton at F1 showed higher ED than at F2. A trend of higher ED values of microzooplankton was observed at the surface than at the near-bottom layer of F1, whereas similar values between both layers (surface and near-bottom) were observed at F2. Mesozooplankton was the plankton fraction that most contributed to the site-depth-time of sampling differences in ED. For instance, the ED of mesozooplankton was higher at the near-bottom than the surface layer during diurnal and nocturnal hours of F1, while the opposite was observed for nocturnal hours at F2. ED of microplankton was associated with conditions of lower values of total alkalinity and salinity but higher temperature, whereas microzooplankton was associated with the opposite conditions. The ED of mesozooplankton was associated with conditions of higher pH and diurnal hours. It is proposed that the energy flow patterns of the plankton community in the Beagle Channel differ in the two micro-basins formed by the MacKinlay Strait (east and west of it), with lower and more homogeneous ED values between fractions and layers east of the Strait characterised by depleted-in-nutrients waters. Fil: ...